Non-Destructive Leaf Area Estimation in Peach - Demirsoy, H.; Demirsoy, L.; Uzun, S.; Kocaman, B. (Int. Soc. Horticultural Science - ISHS, 2004)
In this research, a model for predicting the leaf area was developed for peach by using 'Earlyred', 'Dixired', 'Cardinal', 'Redhaven', 'Glohaven' and 'Cresthaven' cvs. by measuring lamina width, length and leaf area without destroying in 2002. Multiple regression analysis for the cultivars was separately performed. The proposed leaf area (LA) prediction model is: LA=-0.5+0.23*L/W+0.67*L*W, R2=0.9975, LA is leaf area, W is leaf width, L is leaf length. The model was validated by measuring leaf samples of different peach trees of the six cultivars in 2003.
Keywords: Multiple Regression Analysis; Non-Destructive Leaf Area Estimation; Peach